The Influence Of Consumer Decisions On The Desire To Shopping: Easy Of Use And Usefulness - Zuniarti, Ida; Pramularso, Eigis Yani; Kuspriyono, Taat; Winarno, Slamet Heri; Marwansyah, Sofyan; Irawan, Roy; Mustomi, Dede; Rahmiyatun, Fitri (International Journal of Social and Management Studies, 2022)
This study examines the relationship between the desire to shop and consumer decisions. And for the focus of this research is how usability and convenience variables that directly affect the desire to buy and consumer buying decisions. In online purchases, the population is all consumers who have ever shopped online, therefore in the study the number of populations is large and the number is not known precisely, so the researcher decided to make a sampling using random sampling method which is part of the quota sampling technique using respondents aged over 19 years and resides in the Jakarta area. The sample taken amounted to 120 respondents. The results of this study indicate that usability and convenience have a significant and significant effect on consumer spending. Usefulness of use is a variable that has a contribution and influence on the decision to spend. While the desire to buy has a significant and significant effect on consumer decisions to buy. So that the usability factor of a better way and the convenience of the shopping system directly affect consumer decisions.